Tumor-targeted nanomedicines for cancer theranostics. (January 2017) - Arranja, Alexandra G.; Pathak, Vertika; Lammers, Twan; Shi, Yang
Graphical abstract: Abstract: Chemotherapeutic drugs have multiple drawbacks, including severe side effects and suboptimal therapeutic efficacy. Nanomedicines assist in improving the biodistribution and target accumulation of chemotherapeutic drugs, and are therefore able to enhance the balance between efficacy and toxicity. Multiple types of nanomedicines have been evaluated over the years, including liposomes, polymer-drug conjugates and polymeric micelles, which rely on strategies such as passive targeting, active targeting and triggered release for improved tumor-directed drug delivery. Based on the notion that tumors and metastases are highly heterogeneous, it is important to integrate imaging properties in nanomedicine formulations in order to enable non-invasive and quantitative assessment of targeting efficiency. By allowing for patient pre-selection, such next generation nanotheranostics are useful for facilitating clinical translation and personalizing nanomedicine treatments.